2022
DOI: 10.3390/rs14010178
|View full text |Cite
|
Sign up to set email alerts
|

Assimilation of GNSS PWV with NCAR-RTFDDA to Improve Prediction of a Landfall Typhoon

Abstract: Precipitable water vapor (PWV) retrieved from ground-based global navigation satellite system (GNSS) stations acquisition signal of a navigation satellite system provides high spatial and temporal resolution atmospheric water vapor. In this paper, an observation-nudging-based real-time four-dimensional data assimilation (RTFDDA) approach was used to assimilate the PWV estimated from GNSS observation into the WRF (Weather Research and Forecasting) modeling system. A landfall typhoon, “Mangkhut”, is chosen to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Precipitable water vapor (PWV) is a fundamental measurement for quantifying the moisture content within the atmosphere [2][3][4]. Its condensation or energy release, mechanisms contribute to the formation of clouds, rain, snow, and other weather phenomena, thus serving as a crucial energy source for extreme weather events, such as heavy rainfall and typhoons [5][6][7][8][9]. Empirical research has consistently demonstrated a robust correlation between atmospheric PWV and rainfall because the occurrence of precipitation relies on an ample supply of water vapor [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Precipitable water vapor (PWV) is a fundamental measurement for quantifying the moisture content within the atmosphere [2][3][4]. Its condensation or energy release, mechanisms contribute to the formation of clouds, rain, snow, and other weather phenomena, thus serving as a crucial energy source for extreme weather events, such as heavy rainfall and typhoons [5][6][7][8][9]. Empirical research has consistently demonstrated a robust correlation between atmospheric PWV and rainfall because the occurrence of precipitation relies on an ample supply of water vapor [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…There is insufficient research on the parameterization scheme combinations of microphysics, cumulus, and boundary layer. In addition to the selection of parameterization schemes, the assimilation of Global Precipitation Measurement (GPM) microwave and GNSS water vapor can improve the initial and lateral boundary conditions, enhancing the prediction accuracy of typhoon track and intensity [36,37]. Li et al employed a continuous cycling assimilation method to analyze the influence of different Advanced TIROS Operational Vertical Sounder (ATOVS) satellites on the simulation of Typhoon Fanapi [38].…”
Section: Introductionmentioning
confidence: 99%
“…GNSS-derived PWV [13] has gained recognition for its reliability, real-time availability, high temporal resolution, and exceptional accuracy (less than 3 mm) [14]. High-precision GNSS PWV plays a crucial role in monitoring and forecasting extreme weather conditions, such as heavy rainfall [15,16] and typhoons [17,18], while also contributing to the analysis and prevention of natural disasters like earthquakes [19,20] and storm surges [21,22] through the provision of reliable data support Nonetheless, as a relatively recent technique, the retrieval of PWV from GNSS still requires extensive exploration and validation across diverse global spatial and temporal scales.…”
Section: Introductionmentioning
confidence: 99%